Transitioning from Si to SiGe Nanowires as Thermoelectric Material in Silicon-Based Microgenerators - Luis Fonseca; Inci Donmez-Noyan; Marc Dolcet; Denise Estrada-Wiese; Joaquin Santander; Marc Salleras; Gerard Gadea; Mercè Pacios; Jose-Manuel Sojo; Alex Morata; Albert Tarancon (Nanomaterials, 2021)
The thermoelectric performance of nanostructured low dimensional silicon and silicon-germanium has been functionally compared device-wise. The arrays of nanowires of both materials, grown by a VLS-CVD (Vapor-Liquid-Solid Chemical Vapor Deposition) method, have been monolithically integrated in a silicon micromachined structure in order to exploit the improved thermoelectric properties of nanostructured silicon-based materials. The device architecture helps to translate a vertically occurring temperature gradient into a lateral temperature difference across the nanowires. Such thermocouple is completed with a thin film metal leg in a unileg configuration. The device is operative on its own and can be largely replicated (and interconnected) using standard IC (Integrated Circuits) and MEMS (Micro-ElectroMechanical Systems) technologies. Despite SiGe nanowires devices show a lower Seebeck coefficient and a higher electrical resistance, they exhibit a much better performance leading to larger open circuit voltages and a larger overall power supply. This is possible due to the lower thermal conductance of the nanostructured SiGe ensemble that enables a much larger internal temperature difference for the same external thermal gradient. Indeed, power densities in the μW/cm2 could be obtained for such devices when resting on hot surfaces in the 50–200 °C range under natural convection even without the presence of a heat exchanger.